Staging ageing : theatre, performance and the narrative of decline - Mangan, Michael, 1953- (Theatre and consciousness., 2013)
"How can plays and performances, past and present, inform our understanding of aging? Drawing primarily on the Western dramatic canon, on contemporary British theater, on popular culture, and on paratheatrical practices, this book investigates theatrical engagement with aging from the Greek chorus to Reminiscence Theater. It also explores the relationship of the plays, performances, and practices to the material, social, and ideological conditions that produced them. A foundational work on the cultural past and present of aging, the book will find ... audiences not only among scholars but also among theater and health care professionals."--Provided by publisher